2005
DOI: 10.1038/nn1423
|View full text |Cite
|
Sign up to set email alerts
|

G protein βγ directly regulates SNARE protein fusion machinery for secretory granule exocytosis

Abstract: The activation of G protein-coupled receptors (GPCRs) can result in an inhibition of Ca(2+)-dependent hormone and neurotransmitter secretion. This has been attributed in part to G protein inhibition of Ca(2+) influx. However, a frequently dominant inhibitory effect, of unknown mechanism, also occurs distal to Ca(2+) entry. Here we characterize direct inhibitory actions of G protein betagamma (Gbetagamma) on Ca(2+)-triggered vesicle exocytosis in permeable PC12 cells. Gbetagamma inhibition was rapid (<1 s) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
163
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(178 citation statements)
references
References 30 publications
14
163
1
Order By: Relevance
“…Because of the rapidity of release (a few milliseconds), it is unlikely that second messengers are involved in control of the tonic block. Rapid control could potentially be achieved (i) by GPCRs targeting Ca 2ϩ channels (31,34,41), (ii) by GPCRs targeting the release machinery via G ␤ ␥ (11,12,42), or (iii) by a rapid voltagedependent shift of the GPCR affinity and a direct interaction of the GPCR itself with the release machinery (14,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the rapidity of release (a few milliseconds), it is unlikely that second messengers are involved in control of the tonic block. Rapid control could potentially be achieved (i) by GPCRs targeting Ca 2ϩ channels (31,34,41), (ii) by GPCRs targeting the release machinery via G ␤ ␥ (11,12,42), or (iii) by a rapid voltagedependent shift of the GPCR affinity and a direct interaction of the GPCR itself with the release machinery (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…G ␤ ␥ was shown to inhibit transmitter release (11,12) without affecting Ca 2ϩ currents. It is thus possible that PTX exerts its effects by reducing the levels of G ␤ ␥.…”
Section: The Tonic Block Of Release Is Not Mediated By G␤␥mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for the functional significance of this effect in neurons is still scant, although it is known that G protein regulation of N-type channels in chick calyces is altered upon treatment with botulinum toxin C1, 73 and Gβγ subunits have been shown to regulate neurotransmission with their interactions with SNARE complexes. 74 A third regulatory modality linked to the synprint motif is subcellular targeting of the channel. Work from Mochida et al 50,75 shows that the presence of the synaptic protein interaction site is an important determinant of subcellular targeting of P/Q-type channels.…”
Section: Functional Interactions Between Presynaptic Calcium Channelsmentioning
confidence: 99%
“…We have demonstrated that GPCR activation leads to G␤␥ binding to the C-terminal of SNAP-25 in the SNARE complex (2,9,26) at a site coincident with synaptotagmin-SNARE complex binding. Modification of synaptotagmin-SNARE complex interactions can cause incomplete fusion of dense core vesicles (27,28), which may modify neurotransmitter release (17).…”
mentioning
confidence: 93%